Pengaruh Pemberian Buku Saku Pre Hospital Tentang Evakuasi Korban Kecelakaan Lalu Lintas Terhadap Pengetahuan Anggota Pmr Sma Negeri 1 Sokaraja - Resi, Nela Setia; Ramdani, Meida Laely (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Background : Evacuation of traffic accident victims in the pre-hospital stage is giving first aid to the victims in the accident location which is related to moving the victims. Red Cross Youth is a guidance forum from the Indonesian Red Cross whose duty is holding events related to health within the school or community. Improving knowledge of Red Cross Youth members can be done by giving pre-hospital pocketbook about the evacuation of traffic accident victims.Objective : Determining the effect of giving pre-hospital pocketbook about the evacuation of traffic accident victims on the knowledge of SMA Negeri 1 Sokaraja Red Cross Youth members.Method : The research used pre-experimental design through one group pre-test post-test approach. The research test used paired sample t-test involving 40 respondents, taken through total sampling.Results : It is found that giving pre-hospital pocketbook about the evacuation of traffic accident victims has an effect on the knowledge of SMA Negeri 1Sokaraja Red Cross Youth members with the p-value of 0.000.Conclusion : Giving pre-hospital pocketbook about the evacuation of traffic accident victims has an effect in improving the knowledge of Red Cross Youth members of SMA Negeri 1 Sokaraja.